Topological boundaries of covariant representations - Amini, Massoud; Zavar, Sajad (MATHEMATICA SCANDINAVICA, 2023)
We associate a boundary $\mathcal B_{π ,u}$ to each covariant representation $(π ,u,H)$ of a $C^*$-dynamical system $(G,A,α )$ and study the action of $G$ on $\mathcal B_{π ,u}$ and its amenability properties. We relate rigidity properties of traces on the associated crossed product $C^*$-algebra to faithfulness of the action of the group on this boundary.